FUNGSI GEGURITAN PIKUKUH JAGAT - Maharani, Putu Eka (Humanis, 2013)
The research about functions of Geguritan Pikukuh Jagat are aimed to understand the elements of functions, and to analyze how this Geguritan Pikukuh Jagat role in Balinese Hindu community. The main theory of this research was theory of functions. The theory of functions which was used to analyze the implicit functions of Geguritan Pikukuh Jagat was taken bared on some opinions by Luxemburg, Damono, dan Endaswara.In research, methods and techniques was divided into three steps, providing data, analyzing data and presenting data. Providing data used refer method, observe understanding the text with translation technique. Analyzing data used qualitative method, and descriptive analytic technique. Presenting data used the informal method. The functions contained in Geguritan can be used as a religious guidan because geguritan contained ideology of Hindu which can be used by people are the guidelines to behave better, leadership function discusses about how to be a good leader, which has to concern about group necessity rather than selfish necessity. Social function has a function as the guidelines concerned to unity and solidarity in the social life community, also as a comprehension which can be implemented and applied in our daily life. Keyword : geguritan, Pikukuh Jagat, functions 1. Latar
Keywords: geguritan, Pikukuh Jagat, functions